Frameless stereotactic body radiation therapy for multiple lung metastases. (8th July 2014) - Li, Qilin; Mu, Jinming; Gu, Wendong; Chen, Yuan; Ning, Zhonghua; Jin, Jianxue; Pei, Honglei
Abstract : Two patients with multiple lung metastases (≥ 5) were treated using frameless stereotactic body radiation therapy (SBRT) on an Elekta Axesse linear accelerator equipped with an interdigitation‐capable multileaf collimator and four‐dimensional cone‐beam CT (4D CBCT). The technique and the early clinical outcomes were evaluated. Patient A with five lung metastases and Patient B with seven lung metastases underwent SBRT (48 Gy/8 fractions for Patient A, 42 Gy/7 fractions for Patient B). The treatments were administered using a 6 MV photon beam. The nominal dose rate was 660 MUs/min. Patients were positioned and immobilized using thermoplastic masks and image guidance was done using 4D CBCT. The targets were delineated on the images of the 4D CT, and the positron emission tomography‐computed tomography (PET‐CT) images were taken as references. A two‐step, volumetric‐modulated arc therapy (VMAT) plan was designed for each patient. Step 1: the lesions in one lung were irradiated by a 210° arc field; Step 2: the rest of the lesions in the other lung were irradiated by a 120° arc field. Plans were evaluated using conformity index (CI) and homogeneity index (HI). Patients were followed up and adverse events were graded according to the Common Terminology Criteria for Adverse Events v4.0 (CTCAE v4.0). The beam‐on time of each treatment was less than 10 min. The CI and HI for the two plans were 0.562, 0.0709 and 0.513, 0.0794, respectively. Pulmonary function deteriorated slightly in both patients, and the patient with seven lung lesions was confirmed to have Grade 1 radiation pneumonitis. The technique was fast, accurate, and well tolerated by patients, and the two‐step plan is a helpful design in reducing the dose to the lungs. PACS numbers: 87.55‐x, 87.56.J‐, 87.56.‐v, 87.56.nk, 87.57.qp